The tumor-modulatory effects of Caspase-2 and Pidd1 do not require the scaffold protein Raidd - Peintner, L (Cell Death Differ, 2015)
The receptor-interacting protein-associated ICH-1/CED-3 homologous protein with a death domain (RAIDD/CRADD) functions as a dual adaptor and is a constituent of different multi-protein complexes implicated in the regulation of inflammation and cell death. Within the PIDDosome complex, RAIDD connects the cell death-related protease, Caspase-2, with the p53-induced protein with a death domain 1 (PIDD1). As such, RAIDD has been implicated in DNA-damage-induced apoptosis as well as in tumorigenesis. As loss of Caspase-2 leads to an acceleration of tumor onset in the Eμ-Myc mouse lymphoma model, whereas loss of Pidd1 actually delays onset of this disease, we set out to interrogate the role of Raidd in cancer in more detail. Our data obtained analyzing Eμ-Myc/Raidd(−/−) mice indicate that Raidd is unable to protect from c-Myc-driven lymphomagenesis. Similarly, we failed to observe a modulatory effect of Raidd deficiency on DNA-damage-driven cancer. The role of Caspase-2 as a tumor suppressor and that of Pidd1 as a tumor promoter can therefore be uncoupled from their ability to interact with the Raidd scaffold, pointing toward the existence of alternative signaling modules engaging these two proteins in this context.